Integrating Training Pills and Flipped Classroom Model to Enhance B2-Level Writing Skills in EFL Learners: A Quasi-Experimental Study - Felix Martinez, Jose Maria; Safeer, Nadia; Choudhry, Lubna; H. Alaqad, Mohammed (Language, Technology, and Social Media, 2024)
Writing proficiency, especially at the B2 level in English as a Foreign Language (EFL), poses challenges for learners, necessitating mastery of various competencies, including linguistic accuracy and content organization. This study investigates the effectiveness of integrating "training pills" into the Flipped Classroom model to enhance B2-level writing skills. The research adopts a quasi-experimental design conducted over two academic years (2020-2022) in Seville, Spain. The sample consists of 120 high school students, with the experimental group using training pills (short audiovisual lessons), while the control group follows traditional instruction. Pre- and post-tests measured the improvement in writing skills, supplemented by questionnaires assessing satisfaction and engagement. Quantitative data analysis revealed that the experimental group improved by 34.4%, significantly outperforming the control group (11.8%). Qualitative feedback highlighted the accessibility and engagement benefits of the training pills, particularly their role in improving students' organizational and communicative success in writing. The study concludes that training pills, when integrated into a Flipped Classroom model, effectively enhance B2 writing acquisition by providing flexible and self-paced learning opportunities. These findings have significant implications for technology-enhanced learning and offer practical insights for educators seeking to optimize writing instruction for EFL learners.